2015
DOI: 10.1002/alr.21609
|View full text |Cite
|
Sign up to set email alerts
|

Asthma: definitions and pathophysiology

Abstract: Asthma is a chronic inflammatory disorder arising from not fully understood heterogenic gene-environment interactions. It features variable airway obstruction and bronchial hyperresponsiveness. Clinically, asthmatics exhibit recurrent episodes of wheeze, cough, chest tightness, and shortness of breath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
305
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(357 citation statements)
references
References 28 publications
2
305
0
13
Order By: Relevance
“…Asthma is an important and serious public health problem in many countries in the world. Asthma can be mild and doesn’t interfere with the activity, but it can also be persistent and disturbing [13]. Atopic asthma or allergic asthma is asthma based on allergic reaction to the acquisition properties of atopy that found in family and characterized by increased total immunoglobulin E (IgE) or specific IgE.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asthma is an important and serious public health problem in many countries in the world. Asthma can be mild and doesn’t interfere with the activity, but it can also be persistent and disturbing [13]. Atopic asthma or allergic asthma is asthma based on allergic reaction to the acquisition properties of atopy that found in family and characterized by increased total immunoglobulin E (IgE) or specific IgE.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of asthma in Indonesia ranged between 5 and 7%, in global prevalence of asthma ranging from 7 to 10%. According to data from the Center for Diseases Control and Prevention (CDC) National Asthma Control Program in United States 2010 there were 18.7 million adults suffer from Asthma and about nine people die from asthma each day [1, 2, 4, 5]. The prevalence of atopic asthma between 70 and 80% of people with asthma, and about 70–80% of people with asthma also accompanied with allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma is a chronic inflammatory disorder of the airways [30,31]. Our study demonstrated that the level of oxidative stress was increased in mice both immunized and challenged with APE exposed to diesel exhaust, as represented by increased 3-NT expression, resulting in the nitration of various proteins, which enhanced oxidative stress, and provoked activation of NF-κB and production of more inflammatory cytokines and more serious immune imbalance.…”
Section: Discussionmentioning
confidence: 65%
“…These symptoms are typically aggravated by certain environmental triggers, such as smoking, house dust mites, moulds, insects and other animals, pollens, foods, and drugs. 1 In addition to the cardinal symptoms, there are other diagnostic criteria for adult asthma. These include a positive family history of asthma or other allergic diseases, presence of other concurrent allergic diseases, improvement of asthma symptoms after taking asthma medications, as well as the presence of chest wheeze detected by a physician in clinic.…”
Section: Introductionmentioning
confidence: 99%